Pandemics change cities: Municipal spending and voter extremism in Germany, 1918-1933 - Kristian Brickle (Federal Reserve Bank of New York, 2020)
This paper uses several historical data-sets from Germany to show that influenza mortality in 1918-1920 was correlated with (i) lower per-capita spending, especially on services consumed by the young, in the following decade and (ii) the share of votes received by extremist parties in 1932 and 1933. These results are robust when controlling for demographics, population changes, city-level wages, city-level exposure to hyperinflation in 1923, and regional unemployment, and when instrumenting influenza mortality.
Keywords: H3; H4; I15; N14; 330; influenza; pandemic; municipal spending; voter extremism